2021
DOI: 10.1186/s12951-021-01024-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiling of human bone marrow and adipose tissue-derived mesenchymal stem cells reveals differences in osteogenic signaling mediated by graphene

Abstract: Background In the last decade, graphene surfaces have consistently supported osteoblast development of stem cells, holding promise as a therapeutic implant for degenerative bone diseases. However, until now no study has specifically examined the genetic changes when stem cells undergo osteogenic differentiation on graphene. Results In this study, we provide a detailed overview of gene expressions when human mesenchymal stem cells (MSCs) derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…The in vitro results demonstrated that human ADMSCs adhere, proliferate, and cluster on the scaffolds for up to 21 days ( Figure 2 ). These data support our prior studies and publications from other investigators, demonstrating the cytocompatibility and the osteogenic response of goat and human MSCs on graphene films in vitro [ 13 , 14 , 15 , 16 , 17 , 32 ]. The cell behavior also confirms that there are no adverse effects when a 99.95% PLGA blend is used as a binder for the LOG nanoparticles to fabricate a 3D scaffold for in vivo applications.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The in vitro results demonstrated that human ADMSCs adhere, proliferate, and cluster on the scaffolds for up to 21 days ( Figure 2 ). These data support our prior studies and publications from other investigators, demonstrating the cytocompatibility and the osteogenic response of goat and human MSCs on graphene films in vitro [ 13 , 14 , 15 , 16 , 17 , 32 ]. The cell behavior also confirms that there are no adverse effects when a 99.95% PLGA blend is used as a binder for the LOG nanoparticles to fabricate a 3D scaffold for in vivo applications.…”
Section: Discussionsupporting
confidence: 92%
“…This form of graphene is referred to as low-oxygen graphene (LOG). The synthesis and physicochemical properties of LOG nanoparticles have been described earlier [ 15 , 17 , 31 , 32 ]. The physicochemical properties were confirmed to be identical to those reported earlier.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MacDonald et al studied the incubation of human MSCs into a graphene dispersion for 1, 5, 24 and 96 h at 37 • C [134]. The cells were detached with trypsin and centrifuged for 5 min.…”
Section: Graphene Family Combined With Human Mesenchymal Stem Cellsmentioning
confidence: 99%